2021
DOI: 10.3390/biomedicines9091209
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Miniaturized Tuberculosis Spheroid Model

Abstract: Tuberculosis (TB) is a public health concern that impacts 10 million people around the world. Current in vitro models are low throughput and/or lack caseation, which impairs drug effectiveness in humans. Here, we report the generation of THP-1 human monocyte/macrophage spheroids housing mycobacteria (TB spheroids). These TB spheroids have a central core of dead cells co-localized with mycobacteria and are hypoxic. TB spheroids exhibit higher levels of pro-inflammatory factor TNFα and growth factors G-CSF and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, no studies have reported the formation of spheroids using NB4 cells, while THP-1 cells were observed to undergo disaggregation in a previous work, similar to our findings. 37 In this study, THP-1 cells differentiated into macrophages and formed compact spheroids, while the non-differentiated THP-1 cells were in a loose aggregate configuration after 3 d of incubation. Similar results were published with adherent cells, where NIH 3T3 formed a compact spheroid structure starting just 6 h after seeding, while A549 cells resulted in a loose aggregate during the first days of incubation.…”
Section: Resultsmentioning
confidence: 55%
“…To the best of our knowledge, no studies have reported the formation of spheroids using NB4 cells, while THP-1 cells were observed to undergo disaggregation in a previous work, similar to our findings. 37 In this study, THP-1 cells differentiated into macrophages and formed compact spheroids, while the non-differentiated THP-1 cells were in a loose aggregate configuration after 3 d of incubation. Similar results were published with adherent cells, where NIH 3T3 formed a compact spheroid structure starting just 6 h after seeding, while A549 cells resulted in a loose aggregate during the first days of incubation.…”
Section: Resultsmentioning
confidence: 55%
“…Apart from endothelial cells, immune cells can be incorporated. The murine macrophage cell line J774A.1 was used in an M. pneumoniae cell coculture ALI model by Shi et al ( 2023 ), whereas human THP-1 monocytes were used in both ALI and spheroid model infected with M. tuberculosis (Reuschl et al 2017 , Mukundan et al 2021 ). Conversely, Kotze et al.…”
Section: Cell Selection For Pneumonia Modelsmentioning
confidence: 99%
“…Therefore, a validated model that recapitulates TB in human lungs is critical to support TB research. In this regard, a number of in vitro systems ( 176 ), spheroids ( 177 ), human airway organoids ( 178 ), and experimental animal models of TB such as zebrafish ( 179 ), mouse ( 180 ), guinea pig ( 181 ), rabbit ( 182 ) and rat ( 183 ) have provided new insights into the local events that occur during few days and weeks post Mtb infection. In particular, Mtb infection in nonhuman primates closely recapitulates human TB and these models can be used to study the full spectrum of infection outcome and pathology of TB ( 184 ).…”
Section: Innate Immune Responsementioning
confidence: 99%